Synthesis and Preliminary Pharmacological Evaluation of New Analogues of Diclofenac as Potential Anti-inflammatory Agents - H. Naser, Noor; F. Mahdi, Monther; N-A Omar, Tagreed; A. Fadhil, Amar (Iraqi Journal of Pharmaceutical Sciences, 2017)
A group of amine derivatives [4-aminobenzenesulfonamide derivatives, 2-aminopyridine and 2-aminothiazole] incorporated to Î±-carbon of diclofenac a well known non-steroidal anti-inflammatory drug (NSAID) to increase bulkiness were designed and synthesized for evaluation as a potential anti-inflammatory agents with expected COX-2 selectivity. In vivo acute anti-inflammatory activity of the selected final compounds (9, 12 and 13) was evaluated in rats using egg-white induced edema model of inflammation in a dose equivalent to (3 mg/Kg) of diclofenac sodium. All tested compounds produced a significant reduction in paw edema with respect to the effect of propylene glycol 50% v/v (control group). Moreover, the 4-aminobenzenesulfonamide derivative (compound 9) exhibited superior anti-inflammatory activity compared to diclofenac sodium at times 180-300 minutes with the same onset of action. The results of this study indicate that the incorporation of the selected aromatic amino groups in to diclofenac maintain its anti-inflammatory activity. Key words: amine derivatives, anti-inflammatory, diclofenac derivatives, COX-2 selectivity.